Iodine‐Promoted Synthesis of 2‐Naphthyl Thioethers from Tetralones and Sulfonyl Hydrazides. Issue 2 (18th January 2019) - Yang, Fulai; Bao, Yishu; Dai, Zonghao; Tian, Meizhen; Jia, Qian; Zhou, Qingfa
Abstract: In the traditional Bamford‐Stevens‐Shapiro‐type reaction, electrophiles replace the carbonyl group to synthesize polysubstituted carbon‐carbon double bonds. We herein report an unusually simple and general procedure to access carbon‐carbon double bonds from ketones and install electrophiles at the original α‐position of the carbonyl functional group, thus providing a new tool in organic synthesis. This reaction shows a wide substrate scope and functional‐group tolerance. Abstract : Nice and easy : An unusually simple and general procedure to access carbon‐carbon double bonds from ketones is described. Electrophiles are installed at the original α‐position of the carbonyl functional group, thus providing a new tool in organic synthesis.